Industry 4.0: An innovative manufacturing process on a Digital Twin Application - Fajardo-Pruna, Marcelo; Lopez-Estrada, Luis; Sanchez-Orosco, Daniela; Tutiven, Christian; Pillajo-Quijia, Giovanny (EASI: Engineering and Applied Sciences in Industry, 2023)
The fourth industrial revolution requires the process equipment to work together through the strategy of cyber-physical systems. This project aims to contribute to this revolution by presenting a tool and methodology for creating cyber-physical systems. A V-model was used for the design process, in which the digital twin of a 3PRS+XY+C machine tool was developed. It started by defining the requirements, the basis for creating the logical-functional structure. This structure was the guide for completing the behavioural models of each element, the cascade control, and the 3D design of the machine. The simulation was carried out with the digital twin ready to verify the correct operation. A position and speed test were performed with step start and a second order signal showing proper control and compliance with the setpoint. The tests performed show that the strategy used allowed the realisation of the digital twin that conforms to the cyber-physical system of the machine. Also, due to the design mode, the model is highly flexible, and its modular structure facilitates the changes. It is the right time to apply this strategy in the Ecuadorian industry and thus reduce the technological gap and increase international competitiveness.
Keywords: Industry 4.0; Digital Transformation; Micro-Manufacturing; Single Edge Micro-Cutting; Cyber-physical systems